Agricultural waste recycling by farmers: A behavioral study - Pouria Ataei; Hamid Karimi; Zeynab Hallaj; Meysam Menatizadeh (Sustainable Futures)
Agricultural waste recycling is one of the principles of environmental sustainability that is directly associated with farmers’ behavior. In other words, if a farmer decides to recycle her farm wastes, she is moving towards sustainable agriculture goals. This research aimed to explore farmers’ behavioral process for agricultural waste recycling based on the Comprehensive Action Determination Model (CADM). This research was done among farmers in Sistan and Baluchistan province, Iran (N = 6000). The study sample included 361 farmers selected by stratified randomization. The measurement instrument was a self-designed questionnaire. The collected data were analyzed in the SPSS26 and AMOS24 software suites. The results of structural equation modeling (SEM) revealed that farmers’ attitude, social norms, control of subjective constraints, control of objective constraints, and personal norms influenced their intention for agricultural waste recycling significantly. It can be concluded that CADM is a robust instrument for predicting farmers’ behavioral process for agricultural waste recycling, and policymakers and officials of the agricultural sector can use it to enhance farmers’ decision process.